Coadministration of Anastrozole Sustains Therapeutic Testosterone Levels in Hypogonadal Men Undergoing Testosterone Pellet Insertion. (1st January 2014) - Mechlin, Clay W.; Frankel, Jason; McCullough, Andrew
Abstract: Introduction: Current U.S. Food and Drug Administration–approved therapies for hypogonadism involve testosterone (T) replacement. Testosterone pellets (TP) require a minor office procedure every 3 to 4 months. The need for repeated insertions increases the likelihood of a complication. Anastrozole (AZ) is an aromatase inhibitor that has been used off-label for the treatment of male hypogonadism. AZ increases T levels by lowering serum estradiol (E2) levels and increasing gonadotropin (GTP) levels. Aim: We hypothesized that the concomitant use of AZ with TP insertions would sustain therapeutic T levels and increase the interval between TP insertions. Methods: Men treated with TP for hypogonadism at an academic center were offered AZ (1 mg/day) at the time of TP reinsertion as a way of potentially decreasing the frequency of TP insertions. Total T (TT), free T (FT), sex hormone binding globulin, E2, luteinizing hormone (LH), and follicle-stimulating hormone FSH levels were obtained prior to T replacement and at 6 and 15 weeks from TP insertion. Men were re-implanted at 16 weeks if their TT levels were less than 350 ng/dL and their symptoms recurred. We retrospectively reviewed our records of men who underwent TP, TP, and AZ from 2011 to 2012. Demographics, TT, FT, LH, FSH, and E2 levels were recorded. Data were analyzed with anova and a Tukey's test. Main Outcome Measure: TT level at 6, 15, or >15 weeks from TP insertion. Results: Thirty-eight men with 65 insertions were analyzed. The TP AZ group had significantly higher TT and FT levels than the TP group at >120 days ( P < 0.05). The TP group had significantly higher E2 levels at all time points ( P < 0.01). GTP levels remained stable in the TP AZ group. Average time to reinsertion in TP AZ was 198 days vs. 128 days in the TP group. Conclusion: Men on TP AZ maintain therapeutic T levels longer than men on TP alone and have significantly less GTP suppression.